PEMANFAATAN BIODEMULSIFIER UNTUK MENURUNKAN KADAR AIR TERCAMPUR - havidh pramadika; bayu satiyawira; cahaya rosyidan; zakiah darajat (PETRO: Jurnal Ilmiah Teknik Perminyakan, 2021)
Emulsion is one of the problems that is often found in the petroleum production process which needs to be avoided because it can reduce the economic value of oil, the large water content in oil makes the selling price low, even if the water content of the oil is above the standard, the oil may not be accepted in the market. Therefore, this study will try to reduce the water content in the oil, while the formulation of the problem in this study is, knowing whether citric acid from lemon can be used as a demulsifier, knowing what concentration is the most optimal, and knowing whether citral acid from lemon is more optimal than in the NaCl and KCl demulsifier, increasing the concentration of 60% was proven to also increase separate water, where at a concentration of 30% citric acid was the highest to make water separate by 58% while increasing the concentration to 60% was also able to increase water separated by up to 92% minutes 1440 , from that experiment on do the concentration greatly affects the separate water and lemon citric acid can be used as a demulsifier.